FAKTOR PENDORONG DAN FAKTOR PENARIK WISATAWAN MANCANEGARA DALAM MEMILIH DAYA TARIK WISATA SPIRITUAL TIRTA EMPUL KABUPATEN GIANYAR BALI - Dwi Rahayu, Kadek Mayola; Eka Mahadewi , Ni Made; Susianti, Hartanti Woro (Journal of Applied Science in Tourism Destination, 2024)
This research was conducted to determine the push factors and pull factors of foreign tourists in choosing Tirta Empul Spiritual Tourism Attraction. The type of data used is quantitative data with data sources using primary and secondary data. The population in this study are foreign tourists who have visited Tirta Empul Tourist Attraction. The sampling technique uses purposive sampling with a total of 100 respondents. Data collection was done by questionnaire, literature study, and observation. The data analysis technique used Exploratory Factor Analysis using the Statistical Program For Social Science version 25 (SPSS) application program. Based on the study's results, there are 5 driving factors and 2 pull factors for foreign tourist visits to Tirta Empul Spiritual Tourism Attraction. The main factor in the driving factor is Emotional Escape which has a total variance value of 33.623%. while the main factor in the pull factor is the Innovative Exploration factor which has a total variance value of 52.664%.